Investigation of Entropy Generation in Cooling Tower System - Anwar Rizman, Muhammad Syafiq; SIES, MOHAMAD FARID (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Entropy generation in cooling towers is critical to their thermal performance and efficiency. However, reducing entropy formation in cooling towers is crucial since it directly affects the cooling tower’s efficiency and the system’s overall energy usage. Decreased entropy creation results in a more effective cooling process, leading to energy conservation and decreased operational expenses. This study proposes a control volume process that reduces entropy formation in simultaneous heat and mass exchangers. It also aims to investigate the thermal efficiency of a cooling tower system. The experiment uses a Cooling Tower Model HE152 apparatus, uniform PVC packing, and acrylic packing with different water inlet temperatures (35 °C,43°C,50°C) combined with airflow rates of 138 kg/h and water flow rates of 25,50,75,100,125,150, 175 and 200 kg/h. At lower mass flow rates in particular, the system performs best when efficiency and mass flow rate ratio rise; as temperature rises, efficiency falls. In comparing the entropy generation of acrylic and ununiform PVC packing of fill, the study finds that whereas PVC has higher entropy generation because of lower thermal efficiency and higher irreversibilities, acrylic has lower entropy generation, which indicates efficient heat transfer and fewer irreversibilities. The study found that cooling tower efficiency initially increases with mass flow rate but declines beyond this point due to increased turbulence and frictional losses. Acrylic packing shows higher initial efficiency compared with ununiform PVC packing. Entropy generation increased with mass flow rate, reflecting increased irreversibilities due to frictional losses and thermal gradients, particularly at higher temperatures, with acrylic packing exhibiting higher entropy generation.